Economic Empowerment of PKK Groups in Sukamiskin District Through Production and Marketing of Eco-Enzyme Based on Social Entrepreneurship - Nugraha; Patricia, Vinda Maharani; Mardhatillah, Athina (UPT Publikasi Ilmiah UNISBA, 2026)
Abstract. This community service project addresses the critical issue of organic waste accumulation in Sukamiskin Village, Bandung, Indonesia, specifically targeting orange peel waste, which constitutes a significant portion of household refuse. The initiative empowered members of the PKK (Family Welfare Movement) RW 01 group through a structured training program to produce eco-enzyme, a valuable fermented liquid derived from organic waste. The primary goal was to equip 20 PKK members with the technical skills and economic knowledge to transform waste into a marketable, environmentally friendly product. The methodology employed a three-stage process: identification and socialization of the problem and solution, hands-on training in eco-enzyme production, and post-training monitoring and evaluation. A pretest/post-test design using SPSS 22 software confirmed a statistically significant increase in participants' knowledge (p < 0.001). Post-intervention, participants demonstrated practical competence in producing high-quality eco-enzyme, leading to a measurable reduction in household organic waste and the emergence of new micro-enterprises. This project demonstrated that empowering women's groups like the PKK is a highly effective strategy for tackling urban waste management challenges while fostering sustainable economic development at the grassroots level.